2008
DOI: 10.1158/1078-0432.ccr-07-4456
|View full text |Cite
|
Sign up to set email alerts
|

Novel Delivery of SN38 Markedly Inhibits Tumor Growth in Xenografts, Including a Camptothecin-11–Refractory Model

Abstract: Purpose: Clinical development of SN38, the active metabolite of camptothecin-11 (CPT-11), has been hampered due to its poor solubility. We have developed a novel polymer-drug conjugate, EZN-2208, made by linking SN38 with a multiarm polyethylene glycol via a glycine linker. Experimental Design: The in vitro cytotoxicity of EZN-2208 was tested using the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium assay. The therapeutic efficacy of EZN-2208 was evaluated in various xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
148
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(153 citation statements)
references
References 24 publications
3
148
0
2
Order By: Relevance
“…Likewise, the MAG-CPT gave released CPT dynamics of the same type (35,36). However, the polymeric micelle of SN-38 shows the same behavior for released SN-38 in animals (37) and humans (28), as does PEG-bound SN-38 in animals (38) and humans (39). When CPT binding to albumin is properly accounted for, the PK parameters of the unconjugated CPT in animals and humans can be correlated.…”
Section: Discussionmentioning
confidence: 92%
“…Likewise, the MAG-CPT gave released CPT dynamics of the same type (35,36). However, the polymeric micelle of SN-38 shows the same behavior for released SN-38 in animals (37) and humans (28), as does PEG-bound SN-38 in animals (38) and humans (39). When CPT binding to albumin is properly accounted for, the PK parameters of the unconjugated CPT in animals and humans can be correlated.…”
Section: Discussionmentioning
confidence: 92%
“…11 Apoptosis analysis was performed using the annexin V-FITC/propidium iodide assay. (Invitrogen/ Molecular Probes, Eugene, OR, USA) (further details are included in the Online Supplementary Appendix).…”
Section: Antiproliferation Assay and In Vitro Apoptosis Analysismentioning
confidence: 99%
“…10 We have previously shown in pre-clinical models using multiple solid tumors (including a model of in vivo CPT-11 resistance), that EZN-2208 has a significantly enhanced therapeutic index compared with CPT-11. 11 In these studies, EZN-2208 provides higher exposure of tumors to SN38 via the preferential accumulation of EZN-2208 in the solid tumors (enhanced permeability and retention [EPR] effect) compared with CPT-11.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies showed that EZN-2208 was active against several in vivo tumour models that are resistant to CPT-11 and showed prolonged circulation in the blood and thus longer tumour exposure compared to the free drug. 48,49 Moreover, EZN-2208 exhibited antitumour activity against TPT-resistant malignant tumours. 50 A dose-escalation phase I study was conducted to evaluate the safety, tolerability, pharmacokinetics, and activity of EZN-2208 in 39 patients with advanced malignancies (ClinicalTrials.gov identifiers NCT00520637 and NCT00520390).…”
Section: Peg Polymeric Nanoparticlesmentioning
confidence: 99%